The Role of Academic Environment and Capital Access in Fostering Entrepreneurial Interest through Creativity - Ilma Wulansari Hasdiansa; Andika Isma; Hajar Dewantara (CV. Sakura Digital Nusantara, 2025)
Students, as prospective graduates of higher education, play an important role in creating new jobs. This study aims to determine the effect of the academic environment and Capital Access on the entrepreneurial interest of students at the Faculty of Economics and Business, Universitas Negeri Makassar, with creativity as an intervening variable. This quantitative research uses an explanatory descriptive design with a population of all students of the Faculty of Economics and Business, Universitas Negeri Makassar. A sample of 100 people was taken using a proportional random sampling technique. Data were collected using an online questionnaire via Google Form and analyzed using SPSS version 27. The results showed that the academic environment has a positive and significant effect on students' entrepreneurial interest and creativity. Capital Access has a positive and significant effect on student creativity, but has a negative and significant effect on entrepreneurial interest. Creativity has a positive and significant effect on entrepreneurial interest. The academic environment has a positive and significant effect on entrepreneurial interest through creativity. Capital Access has a positive and significant effect on entrepreneurial interest through creativity.